A novel method for detection of lipid oxidation in edible oil. (April 2020) - Xie, Meizhen; Dong, Xiyu; Yu, Yan; Cui, Leqi
Abstract: Lipid oxidation is a major food safety issue for edible oils. The objective of this study was to develop a simple method for detecting lipid oxidation through the color change of a composite film. Schiff's reagent which can form color compound with lipid oxidation products—aldehydes was incorporated into polyvinyl alcohol (PVA) to form the composite film. The effects of PVA molecular weight (Mw), Schiff's reagent/PVA ratio and glycerol content on the response of the composite film to aldehyde were investigated. Sunflower seed oil with various extent of oxidation was used to evaluate the effectiveness of the composite film for lipid oxidation detection. The results showed that the composite film formed with lower PVA Mw turned from colorless to purple upon aldehyde exposure. Higher Schiff's reagent/PVA ratio and glycerol content led to shorter response time and larger color change after aldehyde exposure. The color change of the composite film was linearly (R 2 = 0.96) related to aldehyde concentration. The oxidation status of four sunflower seed oil samples out of five were correctly identified by the composite film. Although the accuracy of this method was 80% in this study, it still shows great potential for lipid oxidation detection application. Highlights: A composite film was developed for detecting lipid oxidation in edible oils. The film turned from colorless to purple when exposed to lipid oxidation product—aldehyde. The film showed high efficiency in identifying highly oxidized edible oil samples.